The role of cognition and reinforcement sensitivity in older adult decision-making under explicit risk conditions. Issue 3 (16th March 2021) - Sinclair, Craig; Eramudugolla, Ranmalee; Brady, Brooke; Cherbuin, Nicolas; Anstey, Kaarin J.
ABSTRACT: Introduction : Previous research has suggested that individual differences in executive functions, memory and reinforcement sensitivity are associated with performance on behavioral decision-making tasks. Decision-making performance may also decline with age, however there is a lack of research on the interplay of cognitive and affective processes, and their impact on older adult decision-making. This study examined associations between executive functions, memory and reinforcement sensitivity on the Game of Dice Task (a measure of decision-making under explicit risk) among older adults. Method : One thousand and two older adults without cognitive impairment (aged 72–78 years) participated as part of an Australian longitudinal cohort study (the Personality and Total Health Through Life study). Decision-making sub-types were identified through cluster analysis and multinomial logistic regression was used to assess associations with measures of cognition and reinforcement sensitivity. Results : Cluster analysis identified three decision-making sub-types, which we label "advantageous, " "disadvantageous" and "switching." Multivariate analyses found that relative to the mid-performing "switching" sub-type, advantageous decision-makers were more likely to be younger, male and have higher scores on a test of verbal learning. Disadvantageous decision-makers were more likely to have poorer scores on some components of executive function (set shifting, but not working memory or inhibitory control), although this effect was partly attenuated by a measure of reinforcement sensitivity (reward responsiveness). Conclusion : These results indicate that specific components of learning and executive functions are influential in decision-making under explicit risk among a sample of older adults.